Transformasi Pastoral Keluarga Katolik dI Era Digital: Sebuah Kajian Literatur Teologis dan Sosial - Muda, Stefanus Dama; Muda, Florianus Pruda (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2025)
The Catholic Church in Indonesia is facing a new reality amid the wave of the digital revolution that has transformed the way people communicate, relate, and live out their faith. This transformation has had a significant impact on Catholic family life, which has long been regarded as the Ecclesia Domestica the first place for faith formation and the nurturing of Christian values. Challenges such as digital secularization, virtual individualism, unequal access to technology, and the culture of instant gratification have urged the Church to renew its pastoral approaches in order to remain relevant and contextual. The transformation of Catholic family pastoral care in the digital era has thus become an essential process to reaffirm the family’s role as a living center of faith formation that is dynamic and responsive to the changing times. Using a qualitative method with a literature study approach, this research explores new directions in Catholic family pastoral ministry in Indonesia and proposes concrete models of accompaniment appropriate to the digital context. The findings reveal four key models that can be pastorally implemented. First, the digital incarnation model, which emphasizes the Church’s active and human presence in the digital world as a means of marturia, koinonia, and diakonia. Second, the digital spiritual literacy model, which fosters families’ critical and ethical awareness in the use of technology. Third, the hybrid pastoral model, which integrates both online and offline engagements to preserve authentic human relationships and sacramental experiences. Fourth, the participatory catechesis model for youth, which encourages young people to become creators of digital faith content rather than passive consumers. The implication of this transformation is the urgent need for collaboration among the Church, families, educational institutions, and lay communities to develop an inclusive, dialogical, and spiritually renewing pastoral practice. Thus, the Catholic Church in Indonesia is called to transform the digital world from a perceived threat into a new space for evangelization and the growth of family faith.